Comparison of Essential Oil Extraction Techniques and Their Therapeutic Applications in Dentistry: Focus on Candida albicans Inhibition - Cuenca-León K; Sarmiento-Ordóñez JM; Pacheco-Quito EM; Benavides-Túlcan SM; Castro NA; Zarzuelo-Castañeda A (Journal of Experimental Pharmacology)
Katherine Cuenca-León,1– 4 Jéssica María Sarmiento-Ordóñez,1,2 Edisson-Mauricio Pacheco-Quito,1,2 Samantha Miriam Benavides-Túlcan,1 Nicole Alejandra Castro,1 Aránzazu Zarzuelo-Castañeda3 1Unidad Académica de Salud y Bienestar, Carrera de Odontología, Universidad Católica de Cuenca, Cuenca, Ecuador; 2Grupo de Investigación Innovación y Desarrollo Farmacéutico en Odontología, Jefatura de Investigación e Innovación, Universidad Católica de Cuenca, Cuenca, Ecuador; 3Department of Pharmaceutical Sciences, University of Salamanca, Salamanca, Spain; 4Red Ecuatoriana de Mujeres Científicas (REMCI) Nodo Univrsidad Católica de Cuenca, Quito, EcuadorCorrespondence: Katherine Cuenca-León, Email kcuencal@ucacue.edu.ecBackground: In this study, the efficacy of three essential oil extraction techniques steam entrainment, Soxhlet extraction, and supercritical fluid extraction (SCF) was evaluated.Aim: Determine the most effective method for obtaining bioactive compounds from Cymbopogon citratus, Origanum vulgare, and Coriandrum sativum, plant species recognized for their antimicrobial and anti-inflammatory properties with potential applications in dentistry. The selected plants, identified based on scientific evidence, were certified and lyophilized prior to extraction. The efficiency of each technique was assessed in terms of essential oil yield, purity, and biological activity.Methodology: The plant species were selected for their therapeutic properties based on scientific reports, certified, and lyophilized before proceeding with the different extraction methods. The efficacy of each technique was compared in terms of the purity and yield of the essential oils obtained. The statistical analysis was performed using SPSS version 25.Results: It was shown that FSC extraction is the method that allows obtaining essential oils with the highest purity and yield, followed by steam entrainment, with the Soxhlet method being the least efficient. However, in the microbiological analysis, the essential oil obtained by steam entrainment showed a greater inhibitory effect against Candida albicans ATCC 90028.Conclusion: In this study, the FSC and steam entrainment techniques are the most suitable for obtaining essential oils for therapeutic applications in dentistry, since they allow better preservation of the bioactive components and reduce the environmental impact. These results position FSC and vapor entrainment extraction as promising options for the development of therapeutic products in dentistry.Keywords: essential oil, extraction methods, odontology, Cymbopogon citratus, Origanum vulgare, Coriandrum sativum